A Sexual Harm? HIV Transmission, 'Biological' GBH and Ancillary Sentencing Provisions in England and Wales. (June 2021) - Giles, Cameron
This article examines the scope and meaning of 'sexual harm' within the context of ancillary sentencing orders in England and Wales. It argues that the statutory definition provided in the Sexual Offences Act 2003, recently replicated in the Sentencing Act 2020, does not extend to the transmission of sexually communicable infections and that, subsequently, it is inappropriate for Sexual Harm Prevention Orders to be imposed with the aim of preventing transmissions of sexually transmitted infections (STIs). It suggests that recent case law reinforces this point and that the questions this raises reflect the broader need for further scrutiny of the aims and purposes of sentencing, and criminalisation more generally, in instances of STI transmission.